2010
DOI: 10.1021/ef100419m
|View full text |Cite
|
Sign up to set email alerts
|

CaO Supported on Porous Carbon as Highly Efficient Heterogeneous Catalysts for Transesterification of Triacetin with Methanol

Abstract: A series of carbon-supported CaO materials, prepared using different porous carbon materials as supports, were tested as basic catalysts for the transesterification of triacetin with methanol and characterized by means of X-ray diffraction (XRD), N 2 adsorption, temperature-programmed desorption (TPD), and X-ray photoelectron spectroscopy (XPS). It was found that all of the carbon-supported CaO catalysts are active for the transesterification reaction, and their catalytic performance can be influenced by a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Although it was found in this study that the effects of the reaction temperature, oil-to-methanol ratio, and reaction time on the efficiency of the transesterification of microalgal oil were similar to those reported in related studies (Dang et al, 2013;Zu et al, 2010), the efficiency obtained in this work was higher than that in the related literature when the reaction was conducted at a low temperature (e.g., 35°C). It is thought that the presence of hexane as a co-solvent played a major role in improving the transesterification efficiency.…”
Section: Transesterificationsupporting
confidence: 81%
“…Although it was found in this study that the effects of the reaction temperature, oil-to-methanol ratio, and reaction time on the efficiency of the transesterification of microalgal oil were similar to those reported in related studies (Dang et al, 2013;Zu et al, 2010), the efficiency obtained in this work was higher than that in the related literature when the reaction was conducted at a low temperature (e.g., 35°C). It is thought that the presence of hexane as a co-solvent played a major role in improving the transesterification efficiency.…”
Section: Transesterificationsupporting
confidence: 81%
“…53 Zu et al 54 have reported two types of "CaO" phases in nanoporous carbon-supported CaO catalysts: the type-I phase has a strong interaction with surface oxygen-containing functional groups of the carbon supports Moreover, some oxygen-containing functional groups exist on the surfaces of carbon support, which would result in surface acidity.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…The active centers in mixed oxides could be either oxygen atoms or the dopants itself. Several research groups were reported that the interaction between CaO and supported [4,22,23] or the formation of binary complex oxide [9,24] improved the catalytic stability. Modification the cation shift in the Ca 2+ -O 2À system enhanced the transesterification processes [3].…”
Section: Introductionmentioning
confidence: 99%